For Women and by Women : The Case of Female Riding-Partner Adoption in Lily Ride, Bangladesh - Tamim Saad, Al Beruny; Helen Tan, Siew Hong (2023)
The advent of the sharing economy has revolutionized various industries, and one sector that has experienced significant transformation is transportation. This paper discusses how the ride-sharing economy, driven by technological advancements and changing consumer preferences, has transformed the way people commute, creating a seamless connection between riding partners and passengers through digital platforms. Specifically, the discussion focuses on the strategic risk perception and female riding-partner (or driver) adoption within the context of female only ride-sharing service, Lily Ride in Dhaka, Bangladesh. Despite the growing popularity of female only ride-sharing services where the riding partners are female, there is a scarcity of female riding partners (or drivers). Thus, the aim of the study is to examine the underrepresentation of female riding partners in traditional ride-sharing services which perpetuates gender disparities in the transportation sector. A conceptual framework for female riding partner adoption is proposed, where the following questions are explored: What are the concerns and strategic risks that are holding potential female riding partners back? Are they lacking financial and societal support? Is there any trust issue that influences their hesitance in becoming a riding partner despite the obvious potential of economic gain? The proposed framework highlights the potential importance of resource support, trust and equitable reward in encouraging and facilitating female participation as riding partners within the male-dominated transportation sector. By providing a platform exclusively for female riding partners, women can participate in the flexible and inclusive income-generating opportunity, in line with the United Nation SDG 5 and the principles of ESG which seeks to empower women.Finally, some thoughts on future research directions and recommendations are also discussed.